2011
DOI: 10.1172/jci57682
|View full text |Cite
|
Sign up to set email alerts
|

Activation of MDL-1 (CLEC5A) on immature myeloid cells triggers lethal shock in mice

Abstract: Systemic inflammatory response syndrome (SIRS) is a potentially lethal condition, as it can progress to shock, multi-organ failure, and death. It can be triggered by infection, tissue damage, or hemorrhage. The role of tissue injury in the progression from SIRS to shock is incompletely understood. Here, we show that treatment of mice with concanavalin A (ConA) to induce liver injury triggered a G-CSF-dependent hepatic infiltration of CD11b + Gr-1 + Ly6G + Ly6C + immature myeloid cells that expressed the orphan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 125 publications
2
53
0
Order By: Relevance
“…We also examined the ability of NRPs to inhibit NETosis induced by other pathogens and found that CRISPP inhibited NET generation stimulated by dengue virus ( Figure 3D). Several viruses trigger NET deployment (43)(44)(45), but dengue, which interacts with ligands on myeloid cells (46), has not previously been reported as having this activity. To further explore the inhibitory activities of nNIF and NRPs, we examined heme, an endogenous damageassociated molecular pattern (DAMP) and toxin (47) that induced NETs in a murine model of sickle cell vasculopathy (17).…”
Section: Crispp and Nnif Inhibit Net Formation Induced By A Spectrum mentioning
confidence: 97%
“…We also examined the ability of NRPs to inhibit NETosis induced by other pathogens and found that CRISPP inhibited NET generation stimulated by dengue virus ( Figure 3D). Several viruses trigger NET deployment (43)(44)(45), but dengue, which interacts with ligands on myeloid cells (46), has not previously been reported as having this activity. To further explore the inhibitory activities of nNIF and NRPs, we examined heme, an endogenous damageassociated molecular pattern (DAMP) and toxin (47) that induced NETs in a murine model of sickle cell vasculopathy (17).…”
Section: Crispp and Nnif Inhibit Net Formation Induced By A Spectrum mentioning
confidence: 97%
“…20 In addition, Cheung et al show that pretreatment of concanavalin A causes the accumulation of CLEC5A ϩ myeloid cells in liver, and incubation of DV with the CLEC5A ϩ myeloid cells causes massive secretion of NO and TNF-␣, whereas myeloid cells from CLEC5A Ϫ/Ϫ mice did not respond to DV infection under the same condition. 48 Thus, the CLEC5A ϩ GM-M subset may also play a critical role in the pathogenesis of DV infection. In contrast to IL-1␤, however, IL-18 is undetectable in both Clec5a ϩ/ϩ Stat1 Ϫ/Ϫ and Clec5a Ϫ/Ϫ Stat1 Ϫ/Ϫ mice after DV infection.…”
Section: Dv-induced Inflammasome Activation Is Via Clec5amentioning
confidence: 99%
“…Blocking DV interaction with MDL-1 reduces vascular leakage and shock in a mouse model of DSS (5). In this issue of the JCI, Cheung and colleagues provide new insights into the characteristics of MDL-1 + myeloid cells and their function in inflammation (6). These data could lead to new approaches for treating multiple conditions characterized by the progression of SIRS to shock and not just DSS.…”
Section: Dengue Shock Syndromementioning
confidence: 99%
“…In this scheme, release of both PMNs and MDL-1 + cells occurs in the bone marrow, under the influence of G-CSF (6). Upon entry into the bloodstream, MDL-1 + cells and PMNs traffic into the liver, which has been injured by injection of ConA.…”
Section: Figurementioning
confidence: 99%